2015
DOI: 10.1016/j.fishres.2015.07.027
|View full text |Cite
|
Sign up to set email alerts
|

Effects of seasonal closures in a multi-specific fishery

Abstract: 27 28In input-controlled multi-specific fisheries, seasonal closure has little biological rationale as a 29 management measure, because it is difficult to adjust such closure for many target species and, in most 30 cases, they are adopted for economic purposes. We aimed to determine effects of closure in biologic and 31 economic terms, using 10-year landing data from two representative trawling ports of the Western 32Mediterranean: Dénia and La Vila Joiosa. Analysis of Variance (ANOVA) was used to detect signi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 31 publications
1
15
0
Order By: Relevance
“…Samy-Kamal et al [23], based on landings data from fisheries operating along the Alicante coast (south-western Mediterranean), concluded that a seasonal closure would have positive biological effects for some target species but this depends on its timing. Merino et al [17], who studied the performance of demersal fisheries in the western Mediterranean, found that only drastic fishing effort reductions (48–71%) in terms of days at sea would improve the health of fish stocks and increase the economic profits of the bottom trawl fishery.…”
Section: Discussionmentioning
confidence: 99%
“…Samy-Kamal et al [23], based on landings data from fisheries operating along the Alicante coast (south-western Mediterranean), concluded that a seasonal closure would have positive biological effects for some target species but this depends on its timing. Merino et al [17], who studied the performance of demersal fisheries in the western Mediterranean, found that only drastic fishing effort reductions (48–71%) in terms of days at sea would improve the health of fish stocks and increase the economic profits of the bottom trawl fishery.…”
Section: Discussionmentioning
confidence: 99%
“…days) VPUE (euro•vessel -1 •day -1 ) of the proposed banning day (selected based on the analysis described in section 2.1). Finally, as the ex-vessel prices significantly decrease by the seasonal closure [5], an additional part of the loss produced by the closure was calculated as the difference between the VPUE (euro•vessel -1 •month -1 ) achieved before and after the closure.…”
Section: Economic Lossmentioning
confidence: 99%
“…trawl fisheries) for a specified period (1-2 months depending on the port and the year). This normally generates problems, because it requires subsidies for vessels owners and crews to compensate this period without revenue, while it also may cause a drop in prices due the market imbalances [5]. Besides the burden of the subsidies on the administration, closure involves an additional problem in the Mediterranean fisheries that have been criticized as most of these subsidies have been transformed into structural compensations [5,6].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations